2022
DOI: 10.3390/medicina58101354
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Abscess Syndrome in Rheumatoid Arthritis Patient

Abstract: Aseptic abscess syndrome (AAS) is a rare, potentially life-threatening disorder, with numerous features of neutrophilic dermatoses. The main symptoms include aseptic abscess-like collections in internal organs (spleen, liver, lungs), lack of microbes (bacteria, viruses, or parasites) after an exhaustive search, ineffectiveness of antibiotics, and high sensitivity to corticosteroid therapy. AAS is characterized by the development of deep, inflammatory abscesses and systemic symptoms (weight loss, abdominal pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, previous studies have linked AAS with intestinal inflammation, particularly in the context of IBD and other autoinflammatory conditions. [1][2][3][4][5][6][7][8] A pervious case report suggested a potential link between AAS and traveler's diarrhea, although in that case, the liver lesions resolved only with heavy immunosuppression, indicating a probable predominant autoinflammatory mechanism in abscess formation. 9 In cases where AAS presented in patients with IBD, favorable responses to immunosuppression and long-term remission with steroid-sparing agents have been observed.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, previous studies have linked AAS with intestinal inflammation, particularly in the context of IBD and other autoinflammatory conditions. [1][2][3][4][5][6][7][8] A pervious case report suggested a potential link between AAS and traveler's diarrhea, although in that case, the liver lesions resolved only with heavy immunosuppression, indicating a probable predominant autoinflammatory mechanism in abscess formation. 9 In cases where AAS presented in patients with IBD, favorable responses to immunosuppression and long-term remission with steroid-sparing agents have been observed.…”
Section: Discussionmentioning
confidence: 92%
“…3,10 Our patient exhibited clinical, endoscopic, and histologic signs of active severe diversion colitis. 8 The pathogenesis of diversion colitis remains uncertain, with proposed mechanisms including deficiencies in short-chain fatty acids or other luminal nutrients, alterations in the colonic microbiome, and changes in mucosal immunity. 11,12 Interestingly, previous case reports showed that diversion colitis may progress into a symptomatic ulcerative colitis-like condition in the diverted colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of aseptic pyomyositis include absence of microbes, bacteria, viruses, and parasites; and poor response to antibiotic therapy [ 1 ]. Rapid clinical improvement after corticosteroid therapy (with colchicine and DMARDs- Disease Modifying Anti-Rheumatic Drugs) is an important feature [ 1 , 2 ]. It is usually associated with autoimmune inflammatory diseases like rheumatoid arthritis (RA), lupus, inflammatory bowel disease [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the association with a steroid-sparing immunomodulator is suggested, considering that longer-term treatments may be required: adalimumab therapy was added in this case at a dose of 80 mg subcutaneously followed by 40 mg every two weeks. Finally, the authors reported that adalimumab therapy was continued even when the patient received remdesivir, following symptomatic SARS-CoV-2 infection without complications [6].…”
mentioning
confidence: 99%